2008
DOI: 10.1016/j.alcohol.2007.12.002
|View full text |Cite
|
Sign up to set email alerts
|

α1-noradrenergic receptor antagonism blocks dependence-induced increases in responding for ethanol

Abstract: The purpose of this study was to test the hypothesis that blockade of α 1 -adrenergic receptors may suppress the excessive ethanol consumption associated with acute withdrawal in ethanol-dependent rats. Following the acquisition and stabilization of operant ethanol self-administration in male Wistar rats, dependence was induced in half the animals by subjecting them to a four-week intermittent vapor exposure period in which animals were exposed to ethanol vapor for 14 hours per day. Subsequent to dependence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
146
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(161 citation statements)
references
References 37 publications
12
146
1
2
Order By: Relevance
“…Interestingly, prazosin was also found to attenuate cocaine-induced reinstatement of cocaine-seeking in rats (Zhang and Kosten 2005) and to inhibit the facilitation of cocaine SA behavior induced by repeated pre-exposure to this psychostimulant (Zhang and Kosten 2007). Likewise, prazosin decreased ethanol SA in ethanol-dependent rats (Walker et al 2008) and reduced cocaine and heroin SA in rats given extended access to these drugs (Greenwell et al 2009;Wee et al 2008). Accordingly, mice lacking the α1B-ARs (α1B-KO) neither developed CPP to morphine nor did they show preference for morphine or cocaine in oral SA paradigm (Drouin et al 2002a).…”
Section: Introductionmentioning
confidence: 89%
“…Interestingly, prazosin was also found to attenuate cocaine-induced reinstatement of cocaine-seeking in rats (Zhang and Kosten 2005) and to inhibit the facilitation of cocaine SA behavior induced by repeated pre-exposure to this psychostimulant (Zhang and Kosten 2007). Likewise, prazosin decreased ethanol SA in ethanol-dependent rats (Walker et al 2008) and reduced cocaine and heroin SA in rats given extended access to these drugs (Greenwell et al 2009;Wee et al 2008). Accordingly, mice lacking the α1B-ARs (α1B-KO) neither developed CPP to morphine nor did they show preference for morphine or cocaine in oral SA paradigm (Drouin et al 2002a).…”
Section: Introductionmentioning
confidence: 89%
“…For example, using animal models of drug self-administration and reinstatement, preclinical studies have shown CRF antagonists and α-2-adrenergic agonists to be efficacious in reducing stress-related drug seeking in addicted laboratory animals (see Shaham et al 2003;Weiss 2005 for review). Similarly, α1-adrenergic antagonists such as Prazosin have been found to decrease alcohol withdrawal symptoms, alcohol consumption and stress-induced relapse in animal models (Gilpin et al 2009;Rasmussen et al 2006;Walker et al 2008) and in a pilot clinical study of alcoholics (Simpson et al 2009). …”
Section: Related Relapsementioning
confidence: 99%
“…We previously demonstrated that prazosin treatment acutely and chronically decreases voluntary alcohol drinking in P rats (Rasmussen et al, 2009;Froehlich et al, 2013), alcohol drinking in a rat model of relapse to alcohol drinking (Froehlich et al, 2015), alcohol seeking and drinking in operant paradigms (Verplaetse et al, 2011), and drinking during acute withdrawal in alcoholdependent outbred rats (Walker et al, 2008). Prazosin treatment also facilitates abstinence in treatment-seeking alcohol-dependent men, as demonstrated in a study in which the subjects were unaware of their treatment condition (prazosin vs placebo) and there were no differences in side effects reported (Simpson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%